2022
DOI: 10.1111/jfbc.14201
|View full text |Cite
|
Sign up to set email alerts
|

Brazil nut supplementation does not affect trimethylamine‐n‐oxide plasma levels in patients with coronary artery disease

Abstract: The purposes of this study were to assess the effect of Brazil nut supplementation on trimethylamine N‐oxide (TMAO) levels and glutathione peroxidase (GPx) activity in patients with coronary artery disease (CAD). Patients with CAD were randomly assigned to two groups, Brazil nut group (23 patients, 48% male, 62.7 ± 6.8 years, 29.4 ± 5.8 kg/m2), which received one Brazil nut per day for 3 months, and the control group (14 patients, 43% male, 63.7 ± 8.7 years, 28.4 ± 4.2 kg/m2) who did not receive any supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Both the tMCAO and tMCAO þ Se groups performed significantly worse than the sham group (Figure 3(f)). However, the number of shock zone entries for the tMCAO þ Se group was significantly lower than that of the tMCAO group (Figure 3(f); 11.17 AE 1.353 vs. 16.83 AE 1.637; P ¼ 0.0173), indicating a long-lasting beneficial effect of selenium supplementation.…”
Section: Delayed Selenium Treatment Rescues Post-tmcao Long-term Cogn...mentioning
confidence: 92%
See 2 more Smart Citations
“…Both the tMCAO and tMCAO þ Se groups performed significantly worse than the sham group (Figure 3(f)). However, the number of shock zone entries for the tMCAO þ Se group was significantly lower than that of the tMCAO group (Figure 3(f); 11.17 AE 1.353 vs. 16.83 AE 1.637; P ¼ 0.0173), indicating a long-lasting beneficial effect of selenium supplementation.…”
Section: Delayed Selenium Treatment Rescues Post-tmcao Long-term Cogn...mentioning
confidence: 92%
“…This observation is in agreement with the results of a recent clinical study which showed that 3 months of selenium supplementation (via the consumption of Brazil nuts) did not reduce the levels of plasma TMA or TMAO in patients with coronary artery disease. 16 Hence, we propose that under an ischemic attack, selenium directly reduces the magnitude of the brain insult, thereby indirectly decreasing stroke-induced TMAO production. Whether inhibition of Enterobacteriaceae leads to a direct reduction in circulating TMAO remains unknown, and the causal relationship with stroke outcomes requires further investigation.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation